Timed and Hybrid Petri Nets at Solving Problems of Computational Intelligence - Čapkovič, František (COMPUTING AND INFORMATICS, 2016)
Timed Petri nets (TPN) and hybrid Petri nets (HPN), more precisely first-order HPN (FOHPN), are used here in order to model, analyse and control discrete-event systems (DES) and hybrid systems (HS) of different kinds consisting of cooperating subsystems (modules, agents). Foremost, principles of the particular kinds of Petri nets (PN), including the primary place/transition PN (P/T PN), are explained. Then, two methods of the supervision are introduced. Finally, the corresponding kinds of PN are applied in four case studies in order to solve the problems of modelling, analysing and control. Namely, the throughput of transport systems (rail and road), flexible manufacturing systems (FMS) and the workflow (WF) of the evacuation process from an endangered area (EA) are handled.